Piezoresistive sensing performance of junctionless nanowire FET - Singh, Pushpapraj (2013)
This letter investigates junctionless nanowire field-effect transistor (NWFET) (JL-NWFET) parameters such as piezoresistance and low-frequency noise (LFN) with respect to channel doping and gate bias. The JL-NWFET is piezoresistive, and its gauge factor (GF ) is increased from 24 to 47 by reducing the channel doping ten times from 6.7 × 1019 to 6.7 × 1018 cm-3. Significant variations of GF and LFN are observed when the JL-NWFET is operated from subthreshold to on-state regime, and resolution (minimum detectable strain) is improved four times compared to inversion-mode NWFET. The simple fabrication and superior resolution formulate JL-NWFET as a promising sensing element for miniaturized nanoelectromechanical sensors.